Regenerierung von Innenstädten unter Schrumpfungsbedingungen. Evaluation eines Städtewettbewerbs und Analyse dessen Rolle für Klein- und Mittelstädte in Sachsen. - Schade, Katrin; Radisch, Susan; Hübscher, Marcus; Ringel, Johannes (Copernicus Publications, 2021)
Many East German cities face long-term shrinking processes, which contribute to declining city centers. This is particularly noticeable in small and medium-sized cities with low human and financial resources. A funding program that helps to regenerate inner cities is the regional city competition „Ab in die Mitte! Die City-Offensive Sachsen“ (AMS) in Saxony, organized as a public-private partnership. This study aims to (1) research AMS concerning its factors of success and obstacles, (2) analyze its role for small and medium-sized cities and, (3) give recommendations to improve AMS. The low-threshold of participation mainly encourages small and medium-sized cities to take part. AMS strengthens exchange and knowledge transfer and promotes endogenous planning strategies. The city competition offers low funding possibilities; therefore, it can only serve as an incentive system. AMS should improve transparency within the evaluation process and, realign its concept to future urban development strategies
Keywords: Kleinstadt; Mittelstadt; Innenstadtentwicklung; Stadtforschung; Schrumpfung; Städtebauförderung; Stadtmitte; Weicher Standortfaktor; Regeneration; Erfolgsfaktor; Projektbegleitung; Handlungsempfehlung; Städtewettbewerb